Influence of the fluidized bed flow regime on the permeate flux in ceramic membrane microfiltration - Mikulášek, Petr (Univerzita Pardubice, 2000)
The influence of a fluized bed on permeate flux during the microfiltration of model disperrions on ceramic membranes has been studied. Following the description of the basic characteristic zirconium dioxide tubular membranes, model dispersions and spherical particles used, some comments about the experimental system, and experimental results for different microfiltration systems are presented. From analysis of experimental results it may be concluded the the use of a fluidized bed resulted in a significant increase of permeate flux in comparsion with results obtained in an empty tube system. This phenomenon is especially pronounced during the microfiltration of oil emulsion when the permeate flux in a fluidized bed system was nearly three times higher. Then, it was found that the optimum porosity of a fluidized bed during which maximal values of permeate flux were reached is in an interval around the value of 0.8. Experimental observations of the onset of aggregate (bubbling) behaviour in liquid fluidized beds are shown to agree with the predictions of a recently published model of the fluidization process. For a given liquid, the transition from particulate to aggregate fluidization process. For a given liquid, the transition from particulate to aggregate fluidization process. For a given liquid, the transition from particulate to aggregate fluidization depends on both the density and size of the fluidized particles.
Keywords: chemické inženýrství; mikrofiltrace; keramické membrány; disperzní modely; fluidní lože; proudění